Infant mortality in Brazil during recent periods of economic crisis - Costa, Maria da Conceição Nascimento; Mota, Eduardo Luiz Andrade; Paim, Jairnilson Silva; Silva, Lígia Maria Vieira da; Teixeira, Maria da Glória; Mendes, Carlos Maurício Cardeal (Revista de Saúde Pública, 2003)
OBJECTIVE: To analyze time trends in infant mortality in Brazil during a recent period of economic crisis (1980-1998). METHODS: Time-series study based on the Ministry of Health's Mortality Information System, IBGE Foundation and Fundação Nacional de Saúde (National Health Institute database. Serial parameters were described using autoregressive integrated moving average (ARIMA) models, and the association between infant mortality rates and a number of determinants was evaluated using Spearman correlation coefficients. RESULTS: Infant mortality showed a declining trend (-59.3%) and a strong correlation with most of the indicators analyzed. However, only correlations between infant mortality rate and total pregnancy and birth rates presented a significant difference between the two decades. CONCLUSIONS: Variations in pregnancy rate were the main cause for the persistent decline in infant mortality in the 1980's. In the subsequent period, causes related to living conditions, especially healthcare, may have been more important.